2006
DOI: 10.1073/pnas.0601674103
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of epigenesis

Abstract: The effect of life stress on depression is moderated by a repeat length variation in the transcriptional control region of the serotonin transporter gene, which renders carriers of the short variant vulnerable for depression. We investigated the underlying neural mechanisms of these epigenetic processes in individuals with no history of psychopathology by using multimodal magnetic resonance-based imaging (functional, perfusion, and structural), genotyping, and self-reported life stress and rumination. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
251
5
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 298 publications
(281 citation statements)
references
References 53 publications
20
251
5
3
Order By: Relevance
“…Using MRI perfusion imaging, Canli and colleagues found support for increased resting activity in the left amygdala and the hippocampus. 102 Similar baseline functional differences are suggested by an acoustic startle study showing that s allele carriers have stronger baseline startle reaction, but do not differ in emotional startle potentiation from ll homozygotes. 103 Furthermore, a whole brain exploration indicates widespread structural and functional differences between s allele carriers and ll homozygotes in other brain regions: the s allele appears to be associated with reduced volume and grey matter density in several frontal-lobe regions, greater reactivity to negative emotional stimuli in the insula and striatum and stronger reactivity to positive emotional stimuli in the left frontal and posterior cingulate regions.…”
Section: Genetic Neuroimagingsupporting
confidence: 62%
See 2 more Smart Citations
“…Using MRI perfusion imaging, Canli and colleagues found support for increased resting activity in the left amygdala and the hippocampus. 102 Similar baseline functional differences are suggested by an acoustic startle study showing that s allele carriers have stronger baseline startle reaction, but do not differ in emotional startle potentiation from ll homozygotes. 103 Furthermore, a whole brain exploration indicates widespread structural and functional differences between s allele carriers and ll homozygotes in other brain regions: the s allele appears to be associated with reduced volume and grey matter density in several frontal-lobe regions, greater reactivity to negative emotional stimuli in the insula and striatum and stronger reactivity to positive emotional stimuli in the left frontal and posterior cingulate regions.…”
Section: Genetic Neuroimagingsupporting
confidence: 62%
“…(2003) appears plausible as it is supported by quantitative population genetics studies, 5 neurophysiological investigations 102 and experimental studies in animals. 26 The majority of replication studies have provided results consistent with such effect (Table 1).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Among younger adults, the interaction between 5-HTTLPR genotype and life stress was significant only when the analysis focused on SLEs that had occurred in the first 5 years of life: individuals homozygous for the L A allele exhibited a negative correlation between the number of SLEs during the first 5 years of life and peak cortisol response to social stress, whereas carriers of the S allele exhibited a positive correlation. Strikingly, a very similar pattern was reported by Canli et al (2006), who in an imaging study observed a negative correlation between SLEs and amygdala activation in homozygous L allele carriers and a positive correlation in S allele carriers (Canli et al, 2006), although these analyses did not separate early SLEs from other SLEs.…”
Section: -Httlpr Sles and Stresssupporting
confidence: 57%
“…The time-course and order of block presentations in the current task also limited our analysis by only being able to use neutral as a baseline condition. We have previously reported on individual differences in resting (fixation) brain activity (Canli et al, 2005(Canli et al, , 2006). In the current series of analysis, we were interested in identifying temporal changes in activity and therefore chose neutral as a baseline based on the comparable timecourse of this condition compared to each of the emotional conditions (4 18-second blocks).…”
Section: Discussionmentioning
confidence: 99%